Soft margin estimation on improving environment structures for ensemble speaker and speaking environment modeling - Li, Jinyu (ACM Proc. the 3rd International Universal Communication Symposium, 2009)
Recently, we proposed an ensemble speaker and speaking environment modeling (ESSEM) approach to enhance the robustness of automatic speech recognition (ASR) under adverse conditions. The ESSEM framework comprises two phases, offline and online phases. In the offline phase, we prepare an environment structure that is formed by multiple sets of hidden Markov models (HMMs). Each HMM set represents a particular speaker and speaking environment. In the online phase, ESSEM estimates a mapping function to transform the prepared environment structure to a set of HMMs for the unknown testing condition. In this study, we incorporate the soft margin estimation (SME) to increase the discriminative power of the environment structure in the offline stage and therefore enhance the overall ESSEM performance. We evaluated the performance on the Aurora-2 connected digit database. With the SME refined environment structure, ESSEM provides better performance than the original framework. By using our best online mapping function, ESSEM achieves a word error rate (WER) of 4.62%, corresponding to 14.60% relative WER reduction (from 5.41% to 4.62%) over the best baseline performance of 5.41% WER.